Thirty years of longitudinal talent development research: a systematic review and meta-aggregation - Dunn, E. L.; Lawrence, G. P.; Gottwald, V. M.; Hardy, J.; Holliss, B.; Oliver, S. J.; Roberts, R.; Woodman, T. (International Review of Sport and Exercise Psychology, 2025)
Talent pathways are longitudinal and multidimensional in nature offering developmental environments for athletes that incorporate multiple processes at multiple timepoints. Recent reviews have unilaterally targeted static talent areas (i.e. talent detection and identification). This review aimed to identify quantitative and qualitative studies with longitudinal designs, within an elite athlete population, that considered development and selection literature collectively. Taking a novel pragmatic approach achieved pluralism in a strive to greatly advance our methodological understanding to acquire knowledge of more effective talent development in sport. This review followed the Preferred Reporting Items for Systematic Review and used a Meta-aggregation methodology. A search of talent development and selection literature identified 41 quantitative and 3 qualitative longitudinal studies. Overall, ten (quantitative) studies investigated interactions between multidimensional selection (i.e. measures of performance) and development characteristics; performance variables changed non-linearly alongside talent development characteristics. No longitudinal mixed-method research studies were found. For practitioners, multiple performance measures need to be considered alongside development characteristics to better assess talent. For researchers, the design of this review models an epistemological and ontological congruent approach that can be used to facilitate the design of future mixed-method and longitudinal research; capturing the dynamic and multifaceted individual differences of talent development.